Improving The Tenth Grade Students’ Writing Skill By Using Picture Series - Pratiwi, Dwi (LPPM Universitas Mercu Buana Yogyakarta, 2016)
AbstractAs a foreign language, English language is not easy to study by students in every grade. Many students cannot understand their materials because they have perception that studying English is very difficult for them. Writing is one of important components in language skills. On the other hand, it is considered difficult by learners including the students of SMA N 1 Sedayu especially class X IIS 3. The students’ writing achievement was still low. To solve this problem, the researcher did the classroom action research. The objectives of this research are describing the improvement of students’ writing skill through recount text using picture series, analyzing the students’ interests in writing skill through recount text using picture series, and finding out how far the improvement of the students using picture series in writing skill through recount text. This research involved 32 students from tenth grade of SMA N 1 Sedayu. In this research, to get the data researcher gave questionnaires, did observation, interview and tests. A classroom action research was used in this research to overcome student’s problem in writing skill. The mean in pre-test and post-test showed a different number. The mean of the pre-test was 61.7 which was still low score because the KKM is 75. Afterwards, the researcher conducted the next treatment, then did post-test and the mean of the students’ score was increased into 77,7. Besides, students also showed different interest in their learning English especially English writing skill.